Infectious mediastinal lymphadenopathy after repeated transbronchial needle aspiration. (29th May 2013) - Hiraishi, Yoshihisa; Goto, Yasushi; Ohishi, Nobuya; Nagase, Takahide
Abstract : A man in his 70s was diagnosed with squamous cell carcinoma (cT1aN2M0) by repeated transbronchial needle aspirations (one conventional and one using endobronchial ultrasonography) of the subcarinal lymph node. Shortly after the initiation of chemoradiotherapy, he began to have chest pain with a high fever. CT showed only subcarinal lymph node swelling. Treatment with several antibiotics was started, and his fever decreased gradually. Chest CT showed shrinking of the subcarinal lymph node, and a diagnosis of infectious lymphadenopathy was made. Infectious lymphadenopathy can be difficult to diagnose because the symptoms are often non-specific and CT findings are not useful in differentiating tumour growth.